Improving Low-Level First-grade Students’ Performance in English in a Heterogeneous Group by Implementing Cooperative Learning (2022)
ABSTRACT : This action research aimed at enhancing low-level students’ English performance in a heterogeneous group through cooperative learning. It was conducted in a public school in La Ceja-Antioquiawith 38-first graders. Action strategies included two stages. The first was based on making detailed observations about the development of English classes and examining the responses students gave to it. The second stage consisted of the use of group activities implementing the action plan. Data gathering instruments included teacher’s journal, Students’ interviews, CT’s interview, and collection of artefacts. Findings revealed the benefits of using cooperative learning, the attitudes, and emotions of students towards it, the role of the teacher when implementing cooperative learning, and the outcomes achieved after this implementation